The "one-group-one-cipher" cryptograph of block-cipher based on chaotic - XUAN Lei1; YAN Ji-ning1 (Tongxin xuebao)
The"one-group-one-cipher"algorithm used the sequence from chaotic mapping as sub-key for block cipher was presented to solve the problem of weak keys existing in currently combined cipher algorithms.The randomness of abstracted key sequence was validated in aspects of Shannon entropy.The"one-group-one-cipher"algorithm was de-signed and implemented based on hyper-chaos generalized Hénon mapping and IDEA algorithms, and its security was analyzed theoretically.Analysis shows that the algorithm is so secure that it can withstand brute force attack, and it was perfect secrecy.The disadvantages of key’s reuse of block ciphers are avoided, and the practicality and feasibility of chaos ciphers and one-time pad are improved.